VD_FINDINFO HC / 2011 / 362 vom 30. März 2011 - VD Tribunal cantonal (2011)
ADMINISTRATEUR OFFICIEL DE LA SUCCESSION, SUCCESSION, BÉNÉFICE D'INVENTAIRE | 553 CC, 489 CPC, 496 al. 2 CPC, 404 al. 1 CPC (CH), 166 al. 2 CDPJ